2017
DOI: 10.1007/s11695-017-2907-z
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Leakage After Laparoscopic Sleeve Gastrectomy: an Analysis of Preoperative and Operative Predictors on 1738 Consecutive Procedures

Abstract: In this large consecutive cohort study of LSG, proximal staple line reinforcement (buttress material or suture) reduced the risk of a leak. The risk of a proximal leak was much higher in the surgeons first 100 cases, which has implications for training and supervision during this "learning curve" period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…As mentioned in Tables 1 and 3, the patients who had a rise in Amylase values didn't differ from the patients who had normal Amylase values in preoperative variables including demographic data or medical background details, as mentioned in other studies [14,24], nor in surgery complications, surgery duration, peri-operative complications nor length of stay in the hospital.…”
Section: Discussionmentioning
confidence: 56%
“…As mentioned in Tables 1 and 3, the patients who had a rise in Amylase values didn't differ from the patients who had normal Amylase values in preoperative variables including demographic data or medical background details, as mentioned in other studies [14,24], nor in surgery complications, surgery duration, peri-operative complications nor length of stay in the hospital.…”
Section: Discussionmentioning
confidence: 56%
“…Shorter than a 2cm distance from pylorus was significantly associated with a high fistula incidence in univariate analysis. 9 On the other hand, Parikh et al couldn't detect an association between the proximity to pylorus and leakage. 10 In the same study, the leakage rate was lower when a bougie equal to or larger than 40F was used.…”
Section: Discussionmentioning
confidence: 98%
“…4,[6][7][8] Cesana et al, evaluated 1738 patients, detected leaks in 45 (2.6%) patients and reported no association between leaks and preoperative variables. 9 The operative variables which were detected to be associated with lower leak incidence included strengthening the staple line and the experience of surgeons. They reported that most of the leaks occurred in the first 100 cases of the surgeons which emphasized the importance of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…The leak rates after sleeve gastrectomy were reported in various rates in the literature, but they are generally low. [8,10,11] Sleeve Gastrectomy Expert Panel Consensus Statement 2011, the leak rate was 1.06%. [12] Surgical intervention may be necessary in cases that cannot be conducted conservatively.…”
Section: Discussionmentioning
confidence: 99%